Inventory management optimization model in a restaurant applying inventory control and lean manufacturing - Salazar Perez, Fabrizio Joaquin (2025)
In recent decades, Peru has experienced a 2.8% GDP growth, thanks to the gastronomic sector. Engaging in the food business has thus become a robust source of income for the country. Despite this, certain companies face internal issues related to the stocks managed by restaurants, as their staff lacks the necessary knowledge to handle inventory. This results in a 9.7% loss of sales within the sector, while the analyzed company incurs a 17% loss. For this reason, this article has developed a solution to this problem in a rotisserie chicken company, which lacks an inventory management system. Studies pinpoint the cause of stockouts to a poor estimation of consumer demand. However, this study consolidated, in addition to consumer behavior, other factors such as the proper planning of raw material purchases, their quality, the level of service provided by the restaurant, and supplier compliance. The results highlight the complexity of avoiding stockouts in a restaurant with a substantial clientele and revealed that designing procurement processes, understanding consumer behavior, and effectively utilizing available spaces are key aspects of successful inventory management. The Value Stream Mapping tool covered 30% of the problem, the inventory management system 50%, and Lean Six Sigma methodologies 20%, respectively.